ANALISIS RISIKO KESEHATAN LINGKUNGAN PENCEMARAN NITRAT (NO3) PADA AIR SUMUR GALI DI KAWASAN PERTANIAN DESA TUMPUKAN KECAMATAN KARANGDOWO KABUPATEN KLATEN - Sinta Nugraheni Dewi; Tri Joko; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
In amount of 67.69% Tumpukan village is an agricultural area where has been contribute nitrate in the groundwater through fertilization activity. The use of urea fertilizer in Indonesia 400-600 kg urea / ha, it exceeds the government's recommendation (200-260 kg urea / ha). The aims of this research is to determine the risk level of exposure nitrate in Tumpukan Village. The research uses a descriptive observational with design study cross sectional and field study ARKL approach. The analysis of data use ARKL method (hazard identification, dose-response analysis, exposure analysis and risk characteristics). The object of population is all wells in the Tumpukan village and the subjects of population are people who use wells for drinking water . The sample object of research is 16 wells were used as sources of drinking water with a distance <50 meters from the area of agriculture and the sample subjects were 89 respondents who use the sample object as sources of drinking water. The results showed an average weight, rate, nitrate's concentration is 52.59 kg and 1.89 liter, 21,26 mg/L. There are nine respondents (10.1%) which have RQ> 1. The conclusion is the risk of nitrate exposure in Tumpukan village is quite low (10.1% of research subjects who are at risk of health problems noncarcinogenic), the risk will appear in the next 10 years for children and 52 years for Adult. The suggestions are farmers can fertilize with organic and inorganic N fertilizer in a balanced way and conducted with the dose and the right time.